Pengaruh Pupuk Kandang Ayam Terhadap Pertumbuhan Vegetatif Tanaman Jagung (Zea mays L.) - Nining Triani Thamrin; Sartia Hama (Yayasan Literasi Sains Indonesia, 2022)
This study aims to determine the effect of giving chicken manure and the right dose in increasing the vegetative growth of maize (Zea mays. L). This research was conducted in March – June 2022 in Sidenreng Rappang Regency using a Randomized Block Design (RAK) with 4 treatments which were repeated 5 times, each replication consisted of 3 sample plants so there were 60 plant units, while the treatments used were N0 : No treatment / no fertilizer, N1: 50 grams of chicken manure, N2: 100 grams of chicken manure, and N3: 150 grams of chicken manure. From the results of the variance of chicken manure giving no significant effect on the vegetative growth of corn plants. There were vegetative growth results that gave the best response with N2 treatment of 100 grams of chicken manure showing plant height = 73.09 cm, stem diameter = 1.14 cm and number of leaves = 7.3 strands.